Impact of Fibrotic Tissue on Shear Wave Velocity in Thyroid: An Ex Vivo Study with Fresh Thyroid Specimens. (31st December 2015) - Fukuhara, Takahiro; Matsuda, Eriko; Endo, Yukari; Donishi, Ryohei; Izawa, Shoichiro; Fujiwara, Kazunori; Kitano, Hiroya; Takeuchi, Hiromi
Abstract : We sought to elucidate the correlation between shear wave velocity (SWV) and fibrosis in thyroid by precisely assessing pathological structures inside 5 × 5 mm 2 regions of interest (ROIs) of resected specimens, under conditions that excluded physical artifacts. The materials were unselected thyroid and lymph node specimens resected during thyroid surgery. Immediately after surgery, fresh unfixed thyroid and metastatic lymph node specimens were suspended in gel phantoms, and SWV was measured. Upon pathological examination of each specimen, the extent of fibrosis was graded as none, moderate, or severe. A total of 109 specimens were evaluated: 15 normal thyroid, 16 autoimmune thyroiditis, 40 malignant nodules, 19 benign thyroid nodules, and 19 metastatic lymph nodes. When all specimens were classified according to the degree of fibrosis determined by pathological imaging, the mean SWV was1.49 ± 0.39 m/s for no fibrosis, 2.13 ± 0.66 m/s for moderate fibrosis, and2.68 ± 0.82 m/s for severe fibrosis. The SWVs of samples with moderate and severe fibrosis were significantly higher than those of samples without fibrosis. The results of this study demonstrate that fibrosis plays an important role in determining stiffness, as measured by SWV in thyroid.